Lenvatinib improves anti-PD-1 therapeutic efficacy by promoting vascular normalization via the NRP-1-PDGFRβ complex in hepatocellular carcinoma - Yang, Jieying; Guo, Zhixing; Song, Mengjia; Pan, Qiuzhong; Zhao, Jingjing; Huang, Yue; Han, Yulong; Ouyang, Dijun; Yang, Chaopin; Chen, Hao; Di, Muping; Tang, Yan; et al. (Frontiers in Immunology, 2023)
The limited response to immune checkpoint blockade (ICB) in patients with hepatocellular carcinoma (HCC) highlights the urgent need for broadening the scope of current immunotherapy approaches. Lenvatinib has been shown to have a synergistic effect with ICBs. However, the optimal strategy for combining lenvatinib with ICB and the underlying mechanisms are not fully understood. This study found that the effect of lenvatinib on promoting tissue perfusion and vascular normalization could not be constantly improved by increasing the therapeutic dose in both immunodeficient and immunocompetent mouse models. An optimal dose was found that more efficiently normalized tumor vasculature and increased immune cell infiltration. The adequate concentration of lenvatinib strengthened the integrity of human umbilical vein endothelial cells. Additionally, lenvatinib promoted the interaction between endothelial cells and pericytes by inducing the formation of the NRP-1-PDGFRβ complex and activated the Crkl-C3G-Rap1 signaling pathway in endothelial cells by inducing tyrosine-phosphorylation in pericytes in vitro. Furthermore, we confirmed that the combination of an optimal dose of lenvatinib and an anti-PD-1 antibody strongly suppressed tumor growth. Overall, our study proposes a mechanism that explains how the optimal dose of lenvatinib induces vascular normalization and confirms its enhanced synergistic effect with ICB.